2006
DOI: 10.1097/01.wnr.0000215770.79281.e4
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic calcification in vitamin D receptor knockout mice

Abstract: Vitamin D is a steroid hormone with many important functions in the brain, mediated through the nuclear vitamin D receptor. Here, we report that aging nuclear vitamin D receptor knockout mice demonstrate a symmetric thalamic calcification with numerous Ca/P-containing laminated bodies. These results are consistent with clinical findings showing brain calcification in patients with vitamin D deficiency. Our results suggest that nuclear vitamin D receptor deficiency leads to brain mineralization in vitamin D rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 25 publications
(55 reference statements)
2
33
0
Order By: Relevance
“…Our previous study also showed that a severe calcification developed in VDR KO mice in the thalamus [Kalueff et al, 2006a] -the brain structure that projects to the inferior colliculus of the auditory pathway and connects with the auditory cortex, as has recently been extensively investigated in both animals and humans [de la Mothe et al, 2006;Devlin et al, 2006;Pearson et al, 2007;Sigalovsky and Melcher, 2006;Takayanagi and Ojima, 2006]. Upon sustaining damage, neuronal retrograde degeneration was observed in the auditory system, and auditory brain stem response (ABR) amplitude decreased after inferior colliculus ablation [Kaga et al, 1999;Yamada et al, 2000].…”
mentioning
confidence: 76%
“…Our previous study also showed that a severe calcification developed in VDR KO mice in the thalamus [Kalueff et al, 2006a] -the brain structure that projects to the inferior colliculus of the auditory pathway and connects with the auditory cortex, as has recently been extensively investigated in both animals and humans [de la Mothe et al, 2006;Devlin et al, 2006;Pearson et al, 2007;Sigalovsky and Melcher, 2006;Takayanagi and Ojima, 2006]. Upon sustaining damage, neuronal retrograde degeneration was observed in the auditory system, and auditory brain stem response (ABR) amplitude decreased after inferior colliculus ablation [Kaga et al, 1999;Yamada et al, 2000].…”
mentioning
confidence: 76%
“…Additionally, Garcion et al [11] demonstrated that vitamin D inhibited the synthesis of inducible nitric oxide synthase, an enzyme produced in CNS cells in response to stress and which in high doses results in neuronal cell death. Finally, the protective properties of vitamin D against mineralization in the human brain should be highlighted [1,21] . Calcium deposits have been described in the basal ganglia of subjects with normal calcemia and phosphoremia alongside hypovitaminosis D.…”
Section: Vitamin D and Brain: The Bases Of A Physiological Relationshipmentioning
confidence: 99%
“…deprived of functional VDR) presented with neuromuscular disorders, hypoacousia, and phosphocalcic homeostasis dysregulation associated with thalamic calcifications [21,24] . Moreover, the absence of VDR in the brain is responsible for behavioral disorders related to anxiety and motor disorders [25][26][27][28][29][30][31] ( table 1 ).…”
Section: Non-senile Hypovitaminosis D and Neuropsychopathological Dismentioning
confidence: 99%
See 1 more Smart Citation
“…55,56 As a possible example of vitamin D deficiency leading to symptoms within the central nervous system, hypoacusis has been documented in rodents deprived of functional vitamin D receptors. 57 Although the mechanism is unclear, vitamin D appears to have a neuroprotective effect on the nervous system 58 promoting an increase in the synthesis of neurotropic agents, 59 an acceleration of neuronal growth, 59 and a protection of neurons against the direct effects of superoxide ions and hydrogen peroxide. 60 Vitamin D also seems to be associated with conduction speeds in the peripheral nervous system.…”
Section: Discussionmentioning
confidence: 99%